Gender transformation in climate-smart agriculture: A framework for action - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presented by Sophia Huyer (CCAFS), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.